Curative treatments for colon cancer during the COVID-19 pandemic era. Issue 4 (August 2022) - Petrelli, Fausto; Labianca, Roberto; Zaniboni, Alberto
During the coronavirus disease 2019 (COVID-19) pandemic, to protect patients with cancer, reduction in hospital access, reduction in myelosuppression risk, and postponing/withholding unnecessary treatments were important in order to reduce risk of infection. Little is known about the risk burden for patients with resected colorectal cancer (CRC). Use of an oral chemotherapy regimen represents a convenient, safe, and manageable therapy for both fit and elderly patients. In the metastatic setting, treatment of solitary metastases may be performed, omitting postresection chemotherapy due to lack of literature data. In case of unresectable CRC, short induction chemotherapy, followed by a maintenance phase, may improve compliance and reduce toxicity. In the adjuvant setting, a shorter duration (3 months) may be discussed with patients except in very high-risk cases. Clinical judgment may reduce the risk of COVID-19 exposure in patients with CRC. Oral regimens, treatment delay, and chemotherapy holiday are ways to minimize the global risk for patients during the COVID-19 era.